2004
DOI: 10.1007/s00330-004-2478-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR imaging of submandibular herniation of sublingual tissues through a gap of the mylohyoid muscle in two cases of submandibular “masses”

Abstract: Except for neoplasms, in symptomatic patients with submandibular swellings, gaps of the mylohyoid muscle may be the cause of herniations of sublingual tissues, such as fat and/or the sublingual gland. In two patients with a submandibular swelling, MRI with standard sequences including contrast enhancement was performed to exclude a neoplastic lesion. In addition, we performed a trueFISP sequence during modified Valsalva's maneuver. In both patients, a neoplasm was excluded. Instead, the trueFISP sequence durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…The classification is as follows: grade 0, normal anatomical structures; grade I, circumscribed thinning of the mylohyoid muscle, vertical reduction in muscle thickness during swallowing, and no signs of glandular penetration; grade II, herniation of the gland during swallowing and normal anatomical structures during rest; and grade III, constant hiatus in the mylohyoid muscle with permanent herniation of the sublingual gland. In that study, almost 20% of the cases were classified as grade II or grade III, whereas 40% showed at least unilateral thinning of the muscle classified as grade I. Keberle et al [9] reported two cases in which functional MRI [true fast imaging with steady state precession (FISP) sequence during the modified Valsalva maneuver] revealed submandibular herniation by the sublingual tissue through a gap in the mylohyoid muscle. The results of these two previous studies suggest that some mylohyoid defects and potential sublingual herniations through mylohyoid defects would be missed on normal static CT, MR, and ultrasound images, and this would be a pitfall.…”
Section: Discussionmentioning
confidence: 96%
“…The classification is as follows: grade 0, normal anatomical structures; grade I, circumscribed thinning of the mylohyoid muscle, vertical reduction in muscle thickness during swallowing, and no signs of glandular penetration; grade II, herniation of the gland during swallowing and normal anatomical structures during rest; and grade III, constant hiatus in the mylohyoid muscle with permanent herniation of the sublingual gland. In that study, almost 20% of the cases were classified as grade II or grade III, whereas 40% showed at least unilateral thinning of the muscle classified as grade I. Keberle et al [9] reported two cases in which functional MRI [true fast imaging with steady state precession (FISP) sequence during the modified Valsalva maneuver] revealed submandibular herniation by the sublingual tissue through a gap in the mylohyoid muscle. The results of these two previous studies suggest that some mylohyoid defects and potential sublingual herniations through mylohyoid defects would be missed on normal static CT, MR, and ultrasound images, and this would be a pitfall.…”
Section: Discussionmentioning
confidence: 96%
“…However, ipsilateral or contralateral compensatory sublingual hypertrophy to compensate for any salivary hypofunction can rarely occur in the absence of one submandibular gland. The hypertrophic sublingual gland may herniate through the mylohyoid gap and causes swelling and pseudomass in the submandibular region …”
Section: Discussionmentioning
confidence: 99%
“…The salivary gland tissue, mass lesions, and the fat tissue may protrude through the gap . It is reported that MRI with fast sequences can provide direct visualization of the mylohyoid gap level and the herniated sublingual tissue during the modified Valsalva maneuver . Although the sublingual gland shows a hyperintense signal on T1‐weighted images, it is often difficult to differentiate the sublingual gland from the fat located in the sublingual space.…”
Section: Discussionmentioning
confidence: 99%
“…It separates the sublingual space superiorly from the submandibular space inferiorly. Swallowing and/or a modifi ed Valsalva maneuver can cause herniation of the sublingual tissue that is confi ned within the mylohyoid muscle in the normal state or can aggravate the severity of the tissue herniation (Keberle et al 2005 ). Additional defects can be frequently observed along the lateral margin of the anterior two-thirds of the mylohyoid muscle (White et al.…”
Section: Herniation Of Sublingual Tissue Through Mylohyoid Defectmentioning
confidence: 99%